2021
DOI: 10.1080/10942912.2021.1950183
|View full text |Cite
|
Sign up to set email alerts
|

Structural, pasting and sensory properties of rice from main and ratoon crops

Abstract: Ratooning was a practical approach to increase the grain yield of rice. In this research, main and ratoon crop rice were compared in quality attributes, including composition, starch morphology, starch crystalline structure, protein components, pasting property, texture, and sensory attributes of cooked rice. As compared to main crop rice, ratoon crop rice showed an increase in amylose content and a decrease in protein content. Both main and ratoon crop rice starches exhibited similar polyhedral shape and A-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Yuan et al [8] found that both the milling and appearance qualities of rice in the ratoon season markedly exceed those of the main season. In a study by Zhang et al [9], the results revealed that the amylose content, as well as the hardness, cohesiveness, adhesiveness, and resilience after cooking, were higher for the rice harvested in the ratoon season, while the protein content was lower when comparing the rice quality characteristics between the main season and ratoon season rice. Additionally, sensory evaluations indicated an overall higher acceptance of rice from the ratoon season compared that from the main season.…”
Section: Introductionmentioning
confidence: 98%
“…Yuan et al [8] found that both the milling and appearance qualities of rice in the ratoon season markedly exceed those of the main season. In a study by Zhang et al [9], the results revealed that the amylose content, as well as the hardness, cohesiveness, adhesiveness, and resilience after cooking, were higher for the rice harvested in the ratoon season, while the protein content was lower when comparing the rice quality characteristics between the main season and ratoon season rice. Additionally, sensory evaluations indicated an overall higher acceptance of rice from the ratoon season compared that from the main season.…”
Section: Introductionmentioning
confidence: 98%
“…Ratoon rice production exploits rice regeneration characteristics. More specifically, certain cultivation and management measures are adopted to induce the germination of the dormant buds on the main rice crop stubble, which is followed by heading, flowering, grain filling and maturity ( Zhang et al., 2021 ). However, in the past, the development momentum has been sluggish for a long time owing to the low yield of ratoon rice.…”
Section: Introductionmentioning
confidence: 99%